2020
DOI: 10.1038/s43246-020-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of complex optical response in Casimir interactions of type I and II Weyl semimetals

Abstract: The Casimir interaction is induced by electromagnetic fluctuations between objects and it is strongly dependent upon the electronic and optical properties of the materials making up the objects.Here we investigate this ubiquitous interaction between Weyl semimetals, a class of 3D systems with low energy linear dispersion and nontrivial topology due to symmetry conditions and stemming from separated energy cones. A comprehensive examination of all components of the bulk conductivity tensor as well as the surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
(71 reference statements)
2
16
0
Order By: Relevance
“…Another place where our results will be useful is the computations of Casimir interaction between Dirac materials (see recent papers [21][22][23][24] and references therein), which are motivated by the exciting possibility to get a repulsive Casimir force. Note, that since the Casimir force is given by a momentum integral, it is important to have expressions for the polarization tensor at all frequencies, as we gave here.…”
Section: Discussionmentioning
confidence: 99%
“…Another place where our results will be useful is the computations of Casimir interaction between Dirac materials (see recent papers [21][22][23][24] and references therein), which are motivated by the exciting possibility to get a repulsive Casimir force. Note, that since the Casimir force is given by a momentum integral, it is important to have expressions for the polarization tensor at all frequencies, as we gave here.…”
Section: Discussionmentioning
confidence: 99%
“…where b 1 , b 2 are the Dirac cone separations of the interacting materials. Since the product b 1 b 2 can be positive or negative as the cone separation can be in positive or negative momentum space domains, the Casimir interaction can be attractive or repulsive [58,59]. Note that the b-parameters, which essentially determine the axion term in the electrodynamics, are continuous.…”
Section: Nontrivial Topology In Materialsmentioning
confidence: 99%
“…This fact renders both plates rotationally symmetric, and we found that this implies that they show a particular response in presence of circularly polarized light: Each photon sees the WSM as an imperfect isotropic mirror, but with a different reflection coefficient depending on its chirality. Even if the gap is filled with vacuum, WSMs exhibit interesting features regarding Casimir interactions, as has been shown in the literature [19,22]. We found that a flipping of one sample in real space may switch the system from repulsive to attractive and vice versa, which makes WSMs very versatile materials from the point of view of investigating the Casimir force, given the fact that the same sample may exhibit either repulsion or attraction depending only on its orientation with respect to another sample.…”
Section: Discussionmentioning
confidence: 69%
“…This symmetry breaking is what allows for the existence of Casimir repulsion, and is what was exploited by Wilson et al [19], who considered a system of two identical time-reversal symmetry breaking WSMs. There is also a very recent work where these results have been extended to type-II WSMs, and include the effect of surface currents [22].…”
Section: Introductionmentioning
confidence: 99%